Helium-induced damage in U3Si5 by first-principles studies. Issue 43 (5th August 2021) - Wang, Yibo; Peng, Zhenbo; Qiu, Nianxiang; He, Heming; Pan, Rongjian; Wu, Lu; Huang, Qing; Du, Shiyu
Abstract : In this paper, helium-induced damage in U3 Si5 was studied by first-principles methods and we revealed theoretical insight into formation of gas bubbles. This work may provide valuable clues for improving the design of UN–U3 Si5 composite fuel. Abstract : Uranium silicide U3 Si5 has been explored as an advanced nuclear fuel component for light water reactor to enhance the accident tolerance. In this paper, in order to understand the fuel performance of U3 Si5, the primary point defects, secondary point defects, and the dissolution of He gas were studied by first-principles methods. Compared with U atoms and another type of Si2 atoms, Si1 atoms far from intrinsic Si vacancies are more likely to form point defects, implying that Si vacancies are prone to form separate single vacancies rather than vacancy clusters in the initial stage. From the calculated anti-site defect energies, it can be predicted that non-stoichiometric U-rich phase of U3 Si5 are more likely to be formed than Si-rich phase, which are consistent with the chemical analysis of experimentally sintered Si-lean U3 Si5 sample. It can be found that a single He atom favors residence in the interstitial site in the U layer directly above/below the intrinsic vacancy. It can also be seen that Vac-U, Vac-Si1, and Vac-Si2 vacancies can energetically accommodate up to 4, 0, and 3 He atoms, respectively. The formation of secondary vacancy defects is strongly dependent on the helium concentration. The current results show that the He-filled vacancy can promote the formation of adjacent secondary vacancy, leading to the formation of gas bubbles. This work may provide theoretical insights into the He irradiation-induced damage in U3 Si5 as well as provide valuable clues for improving the design of the UN–U3 Si5 composite fuel.